Anti-migration in tourism destinations: An interpretation of population changes and the related socio-cultural impacts - Elizabeth A. Cartier (Annals of Tourism Research Empirical Insights)
This study contributes to the understanding of how residents in tourism-based communities were and are being impacted by changes in population due to migration of second homeowners and new full-time residents during COVID-19 where individuals relocated to areas with more space and outdoor amenities. Utilizing semi-structured interviews of the host community in the town of Durango, Colorado, this study proposes that there is a fluid-like cyclical progression of reflecting on development, recognizing internal responses to development, and identifying physical changes related to development such as housing and congestion. The findings of this study suggest that awareness of feelings and actions of anti-migration need to be at the forefront of tourism development decisions to aid in navigating socio-cultural challenges.